2018
DOI: 10.1016/j.molcel.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms for CFIm-Mediated Regulation of mRNA Alternative Polyadenylation

Abstract: Alternative mRNA processing is a critical mechanism for proteome expansion and gene regulation in higher eukaryotes. The SR family proteins play important roles in splicing regulation. Intriguingly, mammalian genomes encode many poorly characterized SR-like proteins, including subunits of the mRNA 3'-processing factor CFIm, CFIm68 and CFIm59. Here we demonstrate that CFIm functions as an enhancer-dependent activator of mRNA 3' processing. CFIm regulates global alternative polyadenylation (APA) by specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
218
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(242 citation statements)
references
References 50 publications
24
218
0
Order By: Relevance
“…We found that 1134 individual PACs were differentially expressed (IHW-padj < 0.1, foldchange >1.5) (Supplemental Data 3). Volcano plots illustrating these changes in gene expression and PAC abundance are shown in The predominant shortening of 3'UTRs upon knock-down of CF25Im is the expected phenotype and is consistent with our and other previous analyses [3,14]. By virtue of measuring differential usage of each individual PAS independently, this pipeline revealed DE of PASs outside of annotated regions.…”
Section: Resultssupporting
confidence: 87%
“…We found that 1134 individual PACs were differentially expressed (IHW-padj < 0.1, foldchange >1.5) (Supplemental Data 3). Volcano plots illustrating these changes in gene expression and PAC abundance are shown in The predominant shortening of 3'UTRs upon knock-down of CF25Im is the expected phenotype and is consistent with our and other previous analyses [3,14]. By virtue of measuring differential usage of each individual PAS independently, this pipeline revealed DE of PASs outside of annotated regions.…”
Section: Resultssupporting
confidence: 87%
“…Some examples of APA changes triggered by Chtop knockdown are presented in Figures 4G and S3C. As a reference, knockdown of Cpsf6 in HEK293T has been reported to lead to 775 significant APA changes (718 distal to proximal and 57 proximal to distal) ( (Martin et al, 2012) data re-analyzed by (Zhu et al, 2018)).…”
Section: Chtop Participates In Apa Regulation In Vivomentioning
confidence: 99%
“…Various human APA trans-regulators have been reported, some directly involved in CPA (Cpsf5, Cpsf6, Cstf2) (Martin et al, 2012;Masamha et al, 2014;Yao et al, 2012;Zhu et al, 2018)1, others linked to splicing (hnRNPC, Tardbp, U2af2, U1 snRNP) (Gruber et al, 2016;…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in which key polyadenylation proteins were knocked down have revealed significant roles for each of them. For example, subunits of mammalian cleavage factor I (CFI m ) have been shown to play important roles in APA, favoring use of distal polyadenylation sites (Li et al, ; Martin, Gruber, Keller, & Zavolan, ; Y. Zhu et al, ). As such, CFI m influences neurite growth (Fukumitsu, Soumiya, & Furukawa, ) and may be involved in glioblastoma (Masamha et al, ).…”
Section: Polyadenylation and Alternative Polyadenylationmentioning
confidence: 99%